The Effect of Different Dielectric Materials in Designing High-Performance Metal-Insulator-Metal (MIM) Capacitors - M. A. Zulkifeli; S. N. Sabki; S. Taking; N. A. Azmi; S. S. Jamuar (Institute of Advanced Engineering and Science, 2017)
A Metal-Insulator-Metal (MIM) capacitor with high capacitance, high breakdown voltage, and low leakage current is aspired so that the device can be applied in many electronic applications. The most significant factors that affect the MIM capacitor’s performance is the design and the dielectric materials used. In this study, MIM capacitors are simulated using different dielectric materials and different number of dielectric layers from two layers up to seven layers. The effect of the different dielectric constants (k) to the performance of the MIM capacitors is also studied, whereas this work investigates the effect of using low-k and high-k dielectric materials. The dielectric materials used in this study with high-k are Al2O3 and HfO2, while the low-k dielectric materials are SiO2 and Si3N4. The results demonstrate that the dielectric materials with high-k produce the highest capacitance. Results also show that metal-Al2O3 interfaces increase the performance of the MIM capacitors. By increasing the number of dielectric layers to seven stacks, the capacitance and breakdown voltage reach its highest value at 0.39 nF and 240 V, respectively.